Transient Femoral Nerve Palsy Complicating "Blind" Transversus Abdominis Plane Block. (4th September 2013) - Manatakis, Dimitrios K.; Stamos, Nikolaos; Agalianos, Christos; Karvelis, Michail Athanasios; Gkiaourakis, Michael; Davides, Demetrios
Abstract : We present two cases of patients who reported quadriceps femoris weakness and hypoesthesia over the anterior thigh after an inguinal hernia repair under transversus abdominis plane (TAP) block. Transient femoral nerve palsy is the result of local anesthetic incorrectly injected between transversus abdominis muscle and transversalis fascia and pooling around the femoral nerve. Although it is a minor and self-limiting complication, it requires overnight hospital stay and observation of the patients. Performing the block under ultrasound guidance and injecting the least volume of local anesthetic required are ways of minimizing its incidence.